REFORMULASI SANKSI PIDANA DALAM TINDAK PIDANA KARTEL - Hersen Monarchy (Kumpulan Jurnal Mahasiswa Fakultas Hukum, 2014)
Abstract Criminal sanctions against perpetrators business of criminal actsÂ cartels contained in Article 48 paragraph (1) of Law No. 5 of 1999 concerning Prohibition of Monopolistic Practices it feels thats no longer effective to be applied at this time. This paper aims to find, analysis, and examine how the philosophical foundations of criminal setting replacement confinement of a criminal offense for cartel and analysis and examine how the reformulation of criminal sanctions against cartel criminal offenses in the future. This paper is based on research that uses the approach of the statute normative approach, conceptual approach, and the comparative approach. The results showed that the selection of criminal sanctions in the form of fines is expected to create a conducive business climate and keep the feeling of anxiety among foreign investors as if every step of business in Indonesia contain the threat of prison where the consequences of coercive imprisonment as efforts are still needed. Supposedly the criminal sanction of a fine replacement in the future reformulated into a supervisory or aggravate criminal sanctions and criminal use of leniency programs or with criminal surveillance. Key words: reformulation criminal acts, cartel Abstrak Sanksi pidana terhadap pelaku usaha tindak pidana kartel yang terdapat dalam pasal 48 ayat (1) Undang-undang Nomor 5 Tahun 1999 tentang Larangan Praktek Monopoli dirasa sudah tidak efektif lagi untuk diterapkan pada masa ini. Tulisan ini bertujuan untuk menemukan, menganilis, dan mengkaji bagaimana landasan filosofis pengaturan pidana pengganti kurungan dalam tindak pidana kartel dan untuk menganilisis dan mengkaji bagaimana reformulasi sanksi pidana terhadap tindak pidana kartel di masa mendatang. Tulisan ini dibuat berdasarkan penelitian normatif yang menggunakan pendekatan statute approach, conceptual approach, comparative approach. Hasil penelitian menunjukkan bahwa landasan filosofis sanksi pidana dalam Pasal 48 ayat (1) UU No. 5 Tahun 1999 adalah sanksi pidana yang berupa pidana denda diharapkan akan menciptakan iklim usaha yang kondusif serta menjauhkan perasaan was-was dikalangan investor asing yang seolah-olah setiap langkah bisnis di Indonesia mengandung konsekuensi ancaman penjara dimana sebagai upaya pemaksa pidana kurungan tetap diperlukan. Semestinya sanksi pidana kurungan pengganti denda di masa mendatang direformulasi menjadi memperberat sanksi pidana dan menggunakan program leniency atau dengan pidana pengawasan. Kata kunci : reformulasi sanksi pidana, tindak pidana kartel, kartelÂ